The Role of Laparoscopy in Emergency Abdominal Surgery - Mandala, Vincenzo (Updates in Surgery,, 2012)
This is the first time a book about laparoscopy in emergency abdominal surgery has been published. Numerous articles have been published in specific surgical journals, but, until now, there has not been a book that collates all the aspects of this little-known field. The aim of this volume is to achieve a complete and easy presentation of all the implications associated with laparoscopy in emergency abdominal surgery. The book should be a manual that can be easily consulted by digestive, general, and specialized surgeons, especially in an emergency. The authors' contributions are founded on evidence-based medicine, which give the book scientific credibility, but this is coupled with their experience of daily practice, which adds an important complementary dimension to evidence-based medicine. This is balanced by an emphasis on clarity and accessibility, because the ultimate aim of the book is educational. We hope this book will be frequently consulted, in depth, not only by specialist practitioners, but also by undergraduate students, new graduates and surgeons in training.